Pencabutan Izin Pemakaian Tanah dan Pelepasan Aset Daerah Berupa Izin Pemakaian Tanah oleh Pemerintah Kota Surabaya - Herpandu Hadiwibowo; Syarifah Fatimahtazzuhrah Rukhsal Assegaf; Alya Fitriani; Amilah Fadhlina (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The Purpose of this study is to analyze the revocation of Land Use Permits (IPT) which have expired and the release of Surabaya City regional assets in the form of IPT. Method of research used in this article is normative legal research using a conceptual approach and a case approach. Based on this research, the following conclusions can be formulated: (1) IPT is a special product released by Surabaya Government through KTUN, so that the Government has the authority to revoke IPT if it does not comply with its intended use, either by providing compensation or without compensation and; (2) IPT as an asset of the city Government can be released by paying a certain amount of compensation with a land release agreement which is regulated in Perwali Surabaya 51/2015.